Sensuous Motion, Sensuous Boundaries, Sensuous Place: Angiolo Mazzoni's Blue Building - Michael McNamara (Oz, 1997)
In his book Archetypes in Architecture, Thomas Thiis-Evensen forges a path between the altars of rational technology and "subjective creativity." His method, which draws closely upon Christian Norberg-Schulz's pioneering research on the architecture of place, is intended to provide a framework for understanding the shared "emotional content" of place through a deep reflection on the nature of the floor, the wall and the roof as the critical elements which convey the existential character of a place.